The hypogean Iberian genus Typhlopsychrosoma Mauriès, 1982 (Diplopoda, Chordeumatida, Vandeleumatidae): distribution map, key to species, first record in a Mesovoid Shallow Substratum (MSS) and detailed iconography of T. baeticaense (Mauriès, 2013) - Gilgado, José D.; Enghoff, Henrik; Ortuño, Vicente M. (Zootaxa, 2015)
The troglobiont millipede Typhlopsychrosoma baeticaense (Mauriès, 2013) is recorded in the Mesovoid Shallow Substratum (MSS) of two screes in the Aitana and Bernia mountains (Eastern Iberian Peninsula), far away from its known distribution area. A detailed Scanning Electron Microscopy iconography provides additional information on gonopod morphology, as well as other details such as the inconspicuous evaginations of the cuticle at the place of the eyes in the anophthalmous specimens. We present an updated distribution map and a key to species of the genus, with illustrations of the gonopods of all species described so far. The implications of the appearance of this hypogean species in an MSS are discussed.